2014
DOI: 10.1021/ef5007758
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Limestone Consumption in Steel Manufacturing Using a Pseudo-catalytic Calcium Lixiviant

Abstract: A mineral carbonation method for using anthropogenic carbon dioxide emissions is discussed. In this method, steel manufacturing slags are carbonated with gaseous carbon dioxide at atmospheric pressure and temperature using an aqueous ammonium chloride solution. This lixiviant extracts calcium selectively from the slag material, after which the dissolved calcium is precipitated as calcium carbonate. A flue gas stream can be used as a CO2 source without pre-separation. The reactions occur pseudo-catalytically in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Specifically, with regard to the latter, significant CO2 uptakes in reasonable timeframes were achieved via the slurry-phase route using residues with a fine particle size (typically below 100 μm), obtained either by milling or simple sieving of the material, and operating the carbonation reactor at enhanced temperature and CO2 pressure (Huijgen et al, 2005;Chang et al, 2012;Santos et al, 2013a,b;Baciocchi et al, 2015). It should be noted, however, that in a recent study, milder operating conditions were shown to be effective employing a proper lixiviant (ammonium chloride) to enhance calcium dissolution (Mattila et al, 2014). Besides, promising results in terms of CO2 uptake (even if lower than those attained through the former route) have been achieved also via the thin-film (or wet) route (Baciocchi et al, 2011(Baciocchi et al, , 2015Santos et al, 2013b;Morone et al, 2014), which is operated at lower temperature and CO2 pressure and also presents the advantage of not generating a liquid by-product that necessitates suitable management and treatment.…”
mentioning
confidence: 99%
“…Specifically, with regard to the latter, significant CO2 uptakes in reasonable timeframes were achieved via the slurry-phase route using residues with a fine particle size (typically below 100 μm), obtained either by milling or simple sieving of the material, and operating the carbonation reactor at enhanced temperature and CO2 pressure (Huijgen et al, 2005;Chang et al, 2012;Santos et al, 2013a,b;Baciocchi et al, 2015). It should be noted, however, that in a recent study, milder operating conditions were shown to be effective employing a proper lixiviant (ammonium chloride) to enhance calcium dissolution (Mattila et al, 2014). Besides, promising results in terms of CO2 uptake (even if lower than those attained through the former route) have been achieved also via the thin-film (or wet) route (Baciocchi et al, 2011(Baciocchi et al, , 2015Santos et al, 2013b;Morone et al, 2014), which is operated at lower temperature and CO2 pressure and also presents the advantage of not generating a liquid by-product that necessitates suitable management and treatment.…”
mentioning
confidence: 99%